XALQARO BUXGALTERIYANI RIVOJLANTIRISH - Zaripova Sayohat Zafarovna, Mamarayimova Sayyora (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
International accounting, as an important part of the global economy, includes the principles and practices necessary to manage financial and accounting processes between different countries. Accounting is basically the process of collecting, processing and presenting financial information. And international journalism refers to the implementation of this process between different countries and cultures. This article provides detailed information on the main principles, problems and practices of international accounting.